SFA Murmurshop - Yahya, Ahmad Faris; Norman, Mohd Arsyad Haidhar; Abdul Rashid, Siti Sahara (2017)
SFAmurmurshop starting with online business we choose to sell caps as we see an opportunities in this industry. We sell various type of cap such as baseball cap, snapback cap, round cap and bucket hat. We choose our product based on the new trend. Our target market is an individual with a group of age from 15 and above. In this industry there are many competitors in online business and for the outlet here in Kota Kinabalu there is The Capcity, Tiptop Bandit and other popular outlet. Moreover the night market also is one of our competitors. In the beginning of our business we target that we can sell 10 caps every month and it will be increase if the market is good. The management of this business we will divide a task for each of our partners, for handling the stock and advertisement will be done by Ahmad Faris, the sales,- promotion and the posting in social media is handle by Mohd Arsyad and the financing and accounting will be handle by Siti Sahara.